Expression and Functional Studies of INS-5, an Insulinase-Like Protein in Cryptosporidium parvum - Ni, Ni; Jia, Ruilian; Guo, Yaqiong; Li, Na; Wu, Haizhen; Feng, Yaoyu; Xiao, Lihua (Frontiers in Microbiology, 2020)
The small Cryptosporidium genome (~9 Mb) has over 20 copies of genes encoding insulinase-like proteases (INS), suggesting that these enzymes may have important biological functions in the pathogen and could be developmentally regulated. In this study, INS-5, a unique member of the INS family in Cryptosporidium parvum, was cloned and expressed in Escherichia coli BL21 (DE3). In addition to the predicted INS-5 of ~78 kDa, smaller fragments of ~70 kDa, ~55 kDa and ~30 kDa were simultaneously generated. After purification through a nickel-nitrilotriacetic acid affinity column, the full recombinant protein obtained was used to prepare polyclonal antibodies. Antibodies raised against INS-5 recognized the recombinant protein and native protein in sporozoite extracts. Further characterization of INS-5 included qRT-PCR assessment of gene expression, immunofluorescence localization of the protein expression in sporozoites, merozoites and other developmental stages, and neutralization of invasion of C. parvum in vitro. The results obtained indicated that although INS-5 was expressed in sporozoites and merozoites, the high gene expression was from 36 h to 48 h of the in vitro culture after invasion. Anti-INS-5 antibodies partially neutralized the invasion (inhibition rate = 38.5%). Results of this study suggest that INS-5 plays some role in the invasion and growth of C. parvum.